Relationship of Role-Play Education with Students’ Scabies Knowledge at the Advent Secondary School Dormitory Noelbaki - Radja, Cindy; Deo, Dwita Anastasia; Wardani, Nimas Prita Rahajeningtyas Kusuma; Koamesah, S. M. J. (Jurnal Biologi Tropis, 2025)
Scabies, a parasitic dermatosis caused by the mite Sarcoptes scabiei var. hominis, is a public health concern in congregate living environments such as dormitories, where suboptimal health literacy facilitates sustained transmission. This quasi-experimental study assessed the efficacy of a role-play-based health education intervention on scabies-related knowledge among adolescent residents of the Advent Secondary School Dormitory in Noelbaki, Central Kupang, Indonesia. Knowledge was measured using a validated 10-item questionnaire administered immediately pre- and post-intervention. Data analysis utilized descriptive statistics and the non-parametric Wilcoxon signed-rank test, with statistical significance defined as p < 0.05. Results demonstrated a significant increase in mean knowledge scores from 50.51 (SD = 15.75) to 91.73 (SD = 9.95). Categorization of knowledge levels revealed a pronounced shift: the proportion of participants with inadequate knowledge declined from 63.3% to 0%, while the proportion with adequate knowledge increased from 7.1% to 89.8%. The Wilcoxon test confirmed a statistically significant improvement in post-intervention scores (p < 0.001). These findings indicate that a targeted, role-play educational intervention is an effective pedagogical strategy for significantly enhancing scabies prevention literacy in high-density residential settings, warranting consideration for integration into broader public health initiatives aimed at mitigating communicable skin diseases.